2022
DOI: 10.1021/acsanm.1c04115
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Fe3O4 Nanoparticle/ZIF-8 Composites for Contaminant Removal from Water and Enhanced Flame Retardancy of Flexible Polyurethane Foams

Abstract: In order to separate heavy-metal ions from contaminated wastewater and further realize the reutilization of waste adsorbent, magnetic composites with flowerlike structure were successfully synthesized. After the absorption of Cu 2+ ions, hybrids can be used as effective coatings to enhance the fire safety of flexible polyurethane foam (FPUF) through a dip-coating method. As-fabricated metal−organic framework (MOF)-based composites exhibited a core−shell and flowerlike structure with high thermal stability. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…In addition, the pure ZIF‐8 has a char residue of ≈30 wt%. [ 46 ] It is expected to have an equivalent amount of residue after the thermal degradation of the composite films. The char residue at 600 °C indirectly reflects the amount of filler on the composite film.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the pure ZIF‐8 has a char residue of ≈30 wt%. [ 46 ] It is expected to have an equivalent amount of residue after the thermal degradation of the composite films. The char residue at 600 °C indirectly reflects the amount of filler on the composite film.…”
Section: Resultsmentioning
confidence: 99%
“…It is noted that the incorporation of basalt wastes and fly ash in the PU matrix led to better thermal stability of the composite foam (hence, higher temperatures of PU thermal decomposition) and higher char yield. Inorganic nanomaterials such as nanoparticles (NPs) are another class of FR additives occasionally used in composite PUFs [ 120 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 ]. For example, silica NPs have been introduced in PUFs via sol-gel deposition [ 187 , 189 ].…”
Section: Other Nanosized Fire Retardantsmentioning
confidence: 99%
“…In these works, a dramatic increase in the fire resistance of final composite foams was achieved owing to the synergetic effect of nanoscale carriers and phosphorous-containing FR ( Figure 11 ). Metal oxide NPs were applied in composite PUFs very recently [ 191 , 192 , 193 ]. The MgO and ZnO NPs added in combination with ATH increased the LOI values of the corresponding PUFs by 3% [ 192 ], whereas modification by CuO-loaded Fe 3 O 4 @ZIF-8 nanocomposite (where ZIF-8 is zeolitic imidazolate framework) decreased both magnetic properties and the pHRR value by 69% [ 193 ].…”
Section: Other Nanosized Fire Retardantsmentioning
confidence: 99%
“…CCT showed that both THR and TSP are reduced, and the mechanical properties are improved [ 153 ]. In addition, there are studies to introduce more metallic elements or flame-retardant elements, and some other properties will be taken into account while enhancing the flame-retardant properties [ 154 , 155 ]. It is suggested that the use of MOFs as derivatives to combine other hybrids, in connection with many other application scenarios, broadens the limits of single use.…”
Section: Mofs As Derivatize Templates and Hybrids With Ldhs As Flame ...mentioning
confidence: 99%